Dejar el pasado atrás o construirle un salvoconducto: disputas teóricas e históricas en torno a la transición a la democracia en Paraguay - Magdalena López (Nuevo mundo - Mundos Nuevos, 2020)
In February of 1989, after more than three decades of mutually beneficial coexistence, Andrés Rodríguez, General of the Army, member of the Colorado Party and part of the family circle, led the overthrow of the dictator Alfredo Stroessner Matiauda. The deposed dictator, after being forced to resign, left the country and went into exile in Brazil until his death. Rodríguez initiated the democratic cycle in Paraguay.In this work, we propose to make a brief review on the theoretical aspects from which the Paraguayan transition was analyzed, the specific forms that it acquired, the strategies that the incipient democracy found to channel the structural crises of the previous regime, and the construction of the constitutional and institutional framework role played in the early nineties.